Structure-induced optical anisotropy in thin films - Horowitz, Flavio (1983)
We consider in this work the contribution of anisotropic microstructure to polarization effects in thin films. The microstructute is pictured by a simple model as composed of identical columns with elliptical cross section elongated in a direction perpendicular to that of the vapor incidence.